Acceleration modules in linear induction accelerators - 王少恒 邓建军 (Chinese physics C, 2014)
The Linear Induction Accelerator （LIA） is a unique type of accelerator that is capable of accelerating kilo-Ampere charged particle current to tens of MeV energy. The present development of LIA in MHz bursting mode and the successful application into a synchrotron have broadened LIA＇s usage scope. Although the transformer model is widely used to explain the acceleration mechanism of LIAs, it is not appropriate to consider the induction electric field as the field which accelerates charged particles for many modern LIAs. We have examined the transition of the magnetic cores＇ functions during the LIA acceleration modules＇ evolution, distinguished transformer type and transmission line type LIA acceleration modules, and re-considered several related issues based on transmission line type LIA acceleration module. This clarified understanding should help in the further development and design of LIA acceleration modules.